2010
DOI: 10.1161/strokeaha.109.577320
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Assessment of Cerebral Autoregulation With Near-Infrared Spectroscopy in Adults After Subarachnoid Hemorrhage

Abstract: Background and Purpose-In patients with subarachnoid hemorrhage, the assessment of cerebral autoregulation aids in prognosis as well as detection of vasospasm. Mx is a validated index of cerebral autoregulation based on measures of cerebral perfusion pressure and mean flow velocity on transcranial Doppler but is impractical for longer-term monitoring. Near-infrared spectroscopy is noninvasive and suitable for continuous monitoring of cerebral tissue oxygenation using the Tissue Oxygenation Index. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 41 publications
(37 reference statements)
4
135
0
3
Order By: Relevance
“…Furthermore, THRT in prospective observational studies was shown to be useful in predicting clinical deterioration after SAH. 2,6 However, while clinical and experimental data exist supporting the validity of Sxa and TOxa, 13,23,25,31,32,34 neither index has been evaluated for its power to predict DCI. The mean flow index, Mx, which is derived from mean FV and CPP and its noninvasive version, Mxa, where ABP is used instead of CPP, have been previously investigated in patients with SAH.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, THRT in prospective observational studies was shown to be useful in predicting clinical deterioration after SAH. 2,6 However, while clinical and experimental data exist supporting the validity of Sxa and TOxa, 13,23,25,31,32,34 neither index has been evaluated for its power to predict DCI. The mean flow index, Mx, which is derived from mean FV and CPP and its noninvasive version, Mxa, where ABP is used instead of CPP, have been previously investigated in patients with SAH.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…(3) Near-infrared spectroscopy-based autoregulation, TOxa, was calculated as a moving, linear correlation coefficient between values of tissue oxygenation index and ABP from a 300-second window with an update every 10 seconds. [23][24][25] The minimum monitoring time required for results to be considered meaningful was 30 minutes.…”
Section: Calculation Of Hemodynamic Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, there was a significant correlation (r = 0.49, p < 0.001) between THx, a measure of autoregulation derived from the total haemoglobin index (measured using spatially resolved spectroscopy with a Hamamatsu NIRO 200) and arterial blood pressure, and the PRx. The same group has also demonstrated a correlation between TOIx, a measure of autoregulation derived from the TOI (Hamamatsu NIRO 200), and the Mx in a group of 27 patients following poor-grade subarachnoid haemorrhage [51].…”
Section: (C) Monitoring Cerebral Autoregulation After Brain Injurymentioning
confidence: 89%